Utilization of E-Learning Based on Learning Management System (LMS) for College Students with Special Needs During Covid-19 Pandemic - Utomo Utomo; Dewi Ekasari Kusumastuti; Misliyani Misliyani (Department of Special Education, 2021)
This study aims to examine the use of E-learning based on LMS for college students with special needs during the Covid-19 pandemic. The method used in this research is a literature study, where the researcher collects relevant data to support the researcher’s ideas. Based on the literature review results, the use of E-Learning based on LMS Edmodo, Schoology, and Learnboost has the same effectiveness despite having different levels of ease of use. Meanwhile, the most frequently used E-Learning based on LMS at the university level is Moodle. In its utilization, E-learning based on LMS has five standard features. So that these five features can be used optimally by students with special needs during the Covid-19 pandemic, things that need to be considered are: (1) particular guidelines for the use of E-Learning based on LMS are available for college students with special needs; (2) audio is available that can be used by college students with visual impairments, (3) sign language is available as an interface so that college students can access it with hearing impairments, (4) available text on lecturer materials in the form of video or audio so that it can be accessed by college students with hearing impairments, (5) there is a virtual keyboard feature available in E-Learning based on LMS which allows college students with physical and motor disabilities to use the mouse to type or do other activities on the computer, (6) the features available in E-Learning based on LMS are designed to accept voice input.